Joint attention with the mother and the father at 10 months of age - Martins, C. (2014)
Joint attention capabilities were assessed in 52 10-month-olds observed independently with their mothers and fathers in a semi-structured toy-play condition. Mothers and fathers were indistinguishable in terms of total number of behaviours aimed at engaging their infant in joint attention. However, infants responded more to mothers' bids for attention than to fathers' bids. Contrastingly, infants tended to display more initiating joint attention behaviours while interacting with their fathers. Although parents did not differ in terms of sensitivity, fathers were less intrusive than mothers. Results are discussed in terms of the specificities of mother-infant and father-infant interaction and how the paternal role should be highlighted in the case of infant's joint attention development.